Eksplorasi Penerapan Sistem Among di Sanggar Anak Alam Yogyakarta - Akbar Al Masjid (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2020)
This study aims to describe the strategy and implementation principles of Ki Hadjar Dewantara about the among systems at Sanggar Anak Alam (Salam) Yogyakarta. This type of research is descriptive qualitative. This research is located in Nitiprayan Kasihan Bantul Yogyakarta. The method used in this study is descriptive qualitative. The researcher investigated the subject by the founder Sanggar Anak Alam, facilitators Sanggar Anak Alam, parents of students. The technique of the collection of data using observation, interviews and , documentation. Moreover, The technique of of the data analysis in this research is through the steps of data collection, data reduction, data display, and verification. Data validation used is source triangulation, technique triangulation, and time triangulation. Research stated that method learning based on research in SALAM planned and agreed by by students, parents and facilitators early in the semester. A method of learning it means that an understanding students built by experience and observation of a phenomenon be her research. The learning methods he continued is very according to the concept in about the hadjar dewantara Â 3Na â€œniteniâ€ phenomenon is looking at. Stages of the implementationÂ  â€œniteni, nirokke, nambahiâ€ in a shrine children nature has been done since an early age school tuition sit in the garden of the child (the becauseÂ  â€œniteni nirokke nambahiâ€ itself is step in the process of learning carried out school tuition with research activities. The "asah, asih, asuhâ€Â  factor carried out by the facilitator and parents is very influential in student learning activities. So that the nature of "ngemong" and "tlaten" is always needed to guide and motivate students. Familiarity and closeness of the facilitator in guiding their students in a patient way and nurturing habits that are liked and disliked by students also become the facilitator's attention in creating a fun education according to the child's nature (interests and their talents).